Trainer Performance through Service Quality Drives MSME Sales Growth in Indonesia’s Creative Sector - Ida Nuraida; Devi Roza Krisnandhi Kausar; Bambang Sugiharto; Yuwana Marjuka (International Research Journal of Business Studies, 2026)
This study examines the effectiveness of integrated training components in enhancing sales performance among micro, small, and medium-sized enterprises (MSMEs) in Indonesia’s creative economy. Addressing a gap in prior research, it introduces trainer service quality as a distinct construct representing trainer performance. Other training components assessed include structured modules, bookkeeping workshops, business laboratories, and marketing training. Researchers analyzed data from 75 MSME participants across 31 sub-districts in Bandung Regency using Structural Equation Modeling (SEM) with AMOS. The results indicate that trainer service quality is the most influential factor in improving sales performance. Structured modules and hands-on workshops also contribute significantly when delivered effectively. This study validates a multidimensional model of training effectiveness in a developing country context and provides practical recommendations. Managerial implications include improving trainer quality, strengthening training infrastructure, and promoting collaboration among government, academia, and MSMEs to support inclusive, sustainable economic development